To Determine the Frequency of Maternal and Fetal Outcomes of Uterine Rupture at a Tertiary Care Hospital (Medical Forum Monthly, 2021)
Objective: To determine the frequency of maternal and fetal outcomes of uterine rupture at a tertiary care hospital.Study Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the department of Gynae/Obstetrics Unit-I Sandeman Provincial Hospital Quetta for 10 months. January 2020 to October 2020.Materials and Methods: The total sample size was 126 patients which were consecutively enrolled were having presenting with uterine rupture. Cases of ruptured uterus, who were either admitted with or who will develop this complication in the hospital, were included in the study. Diagnosis was made on history and examination and was confirmed on laparotomy. These cases were analyzed with regard to their clinical presentation, past history complications, management and outcome were noted as maternal mortality and perinatal outcome were still birth, early neonatal death, alive and perinatal mortality. The surgical procedure depended on general condition of the patients, parity, and desire for future child bearing, site, severity and extent of rupture.Results: A total of 126 women having uterine rupture were enrolled in this study. Mean age was 29.58± 876(SD), Mode was 29, and Median was 28.5 with ranging between (16-45) years. Ranged between 16 to 45 years, the maximum number of cases 76(60.3%) were less than 30 years of age. This shows that according to this study uterine rupture was more common at the age <30 years. Regarding the parity, majority of patients 73[57.9%] in this study were primigravidas, followed by 49[3.9%] in parity group of multigravida, only four cases having follow on multigravida. Most of the cases coming in our hospital were un-booked accounted for 81[64.3%]. Regarding the risk factors in current pregnancy in women presenting with uterine rupture was most of the commons was observed Scarred Uterus 22[17.5%] and Scarred uterus with spontaneous labour was 25[19.8%]. Some cases follow Scarred uterus with augmentation with syntocinon was 11[8.7%] Transverse lie was 10[7.9%]. No risk factor could be identified in Scarred uterus with induction with prostaglandin E2. Maternal morbidity in women with uterine rupture was identified as in women having shock was 41[32.5%], 27 [21.4%] were anemic, 22 [17.5%] had Puerperal Sepsis, Whereas DIC was presented in 13[10.3%] respectively. Perinatal mortality was 15 [11.9%]. Regarding neonatal morbidity or alive was 47 [37.3%], fifty patients was still birth respectively.Conclusion: This study concluded that prolonged neglected obstructed labour is the main cause of ruptured uterus followed by scarred uterus. Proper antenatal care and updated training courses of health care providers should be stressed to prevent this catastrophic but avoidable complications. Regular antenatal care, hospital deliveries and care during labor with quick referral to well-equipped hospitals may reduce the incidence of this condition.